Prove

Asked by  | 27th Aug, 2008, 09:24: PM

Expert Answer:

let y = (23+3)sinθ + 23cosθ

multiply and divide by a where a= ( (23+3)2 + (23)2 )1/2 = ( 33+123 )1/2

y = a ( ( (23+3)/ a)sinθ + (23/ a)cosθ )

= a sin(θ + b)

where sin b = (23/ a) and cos b = (23+3)/ a

so clearly y will vary between - a and a. since sin(θ + b) varies between -1 and 1

so i think there is some error in this question.

so please check and repost it.

Answered by  | 12th Sep, 2008, 03:04: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.